Evaluasi Penerapan Aplikasi SILETON dalam Pelayanan Administrasi Masyarakat di Nagari Magek - Andrizal Andrizal; Yulianingsih Yulianingsih; Rizan Hasbullah (ARZUSIN, 2026)
Digitalization of public administration in rural areas often faces a gap between policy ambitions and field realities, particularly when electronic service innovations are not accompanied by adequate resource and infrastructure readiness. This study aimed to evaluate the implementation of the SILETON application (Integrated Online Electronic Service Information System) in Nagari Magek, Agam Regency, West Sumatra Province, in order to assess the achievement of efficient, transparent, and broker-free public service goals. This study used a descriptive qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model from Stufflebeam and Zhang (2017). Data were collected through in-depth interviews, observation, and documentation involving 26 informants consisting of nagari officials, jorong heads, and community members who used the service. The results showed that in the context aspect, the SILETON program was relevant to service needs and supported by strong regulations, but it still faced limited infrastructure and low digital literacy among the community. In the input aspect, structural deficits were found in the form of the absence of human resource training, the lack of a dedicated budget, and internet network instability. In the process aspect, program socialization remained very limited, having been conducted only twice compared with the ideal condition of five to seven times, thereby resulting in low service adoption and the continued prevalence of brokerage practices. In the product aspect, SILETON improved efficiency for active users, but the Community Satisfaction Index only reached 73 out of 100, with digital penetration of 2–2.4% per month of the total number of households. The conclusion of this study confirms that SILETON’s partial failure stemmed more from non-technical factors than from weaknesses in the technology itself. The implications of this study indicate that the success of nagari-level e-government requires simultaneous investment in human resource capacity, operational standardization, and inclusive digital infrastructure, while also confirming that top-down technological mandates without proportional resource transfer can become an unfunded mandate that exacerbates public service inequality.